Utilization of thermite energy for re-entry disruption of detachable rocket elements made of composite polymeric material. (September 2018) - Monogarov, K.; Trushlyakov, V.; Zharikov, K.; Dron, M.; Iordan, Yu; Davydovich, D.; Melnikov, I.; Pivkina, A.
Abstract: A conceptual approach to improve the safety of rocket-space activity is presented, including minimization of space debris returning from space. The main idea is to eliminate hazards of uncontrolled re-entry of detachable rocket design elements after finishing their mission with the use of the energy of pyrotechnic thermite reaction to disrupt these parts made of composite polymeric material, i.e., carbon fiber reinforced polymer. As an example, the payload fairing half is considered, the conditions for its descent in dense layers of the atmosphere are calculated. Results reveal that depending on the entrance velocity, the target object or completely burn out, or the additional heat source is required for its full destruction. It is proposed that pyrotechnic composition to be installed on the object could serve as additional heat source to provide its combustion or fine dispersion during the atmospheric re-entry phase of the descent trajectory. The possible pyrotechnic compositions to be used are presented and discussed. Highlights: Re-entry conditions for detachable rocket elements are calculated. At entrance velocity 2 km/s the additional heat source is required for destruction. Thermal modelling reveals pyrotechnic composition to be additional heat source. Amount of pyrotechnic charge to disrupt composite polymeric material is estimated.